2011
DOI: 10.2146/ajhp100217
|View full text |Cite
|
Sign up to set email alerts
|

Effect of serum sodium concentration and tolvaptan treatment on length of hospitalization in patients with heart failure

Abstract: A secondary analysis of a large, international, Phase III trial of patients hospitalized for HF demonstrated that comorbid hyponatremia was associated with a significant increase in hospital LOS. Treatment of hyponatremia with tolvaptan was associated with reductions in LOS that were not significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…23) Consistently, responders with TLV had significantly shorter LOS compared with those without TLV during the 1-year study period. As Chiong, et al and Dasta, et al reported in the EVEREST trial sub-analysis and SALT-1/SALT-2 trials subanalysis, shorter LOS during TLV therapy may dominantly contribute to a reduction in the total medical expenses.…”
Section: )mentioning
confidence: 60%
“…23) Consistently, responders with TLV had significantly shorter LOS compared with those without TLV during the 1-year study period. As Chiong, et al and Dasta, et al reported in the EVEREST trial sub-analysis and SALT-1/SALT-2 trials subanalysis, shorter LOS during TLV therapy may dominantly contribute to a reduction in the total medical expenses.…”
Section: )mentioning
confidence: 60%
“…Post hoc analyses of Phase III trials evaluating tolvaptan efficacy and safety for the treatment of hyponatremia found that patients administered tolvaptan had a decreased LOS in comparison with patients who were administered placebo (Table 4) [49,50]. The post hoc analysis of the EVEREST trial found that patients with hyponatremia had a hospital LOS that was on average 3 days longer in comparison with patients not diagnosed with hyponatremia, but patients with hyponatremia administered tolvaptan had a 15% decreased LOS in comparison with patients with hyponatremia given placebo (patients with baseline serum sodium concentrations of <135 mEq/l had a 1.72 day decrease, p = 0.06; patients with baseline serum sodium concentrations of <130 mEq/l had a 2.12 day decrease, p = 0.58).…”
Section: The Economic Burden Of Hyponatremia and Potential Impact Of Tomentioning
confidence: 99%
“…The number of heart failure patients with hyponatremia was estimated to be 11.5% based on the study of Chen et al [15], and the LOS reduction was estimated as 15% based on the EVEREST post hoc analysis [49]. The total hospital costs and LOS among the study population were derived from the HCUPnet database.…”
Section: Drug Profilementioning
confidence: 99%
“…The analysis was conducted from the perspective of hospitals in the US. The potential cost reduction due to tolvaptan use was derived from the LOS reduction determined in a post-hoc EVEREST trial analysis and was applied to the associated costs and resource usage of a US study population from the 2008 Nationwide Inpatient Sample (NIS) database consisting of hospitalized adult HF patients 19 . Univariate and multivariate Monte Carlo sensitivity analyses were performed as components of the economic model to evaluate the range of the potential cost reduction associated with tolvaptan due to variation in the estimated model parameters.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Post-hoc analysis determined that the use of tolvaptan was also associated with a decrease in the LOS of CHF patients 19 . The primary objective of this study was to evaluate the potential hospital cost savings associated with tolvaptan usage among HF patients with hyponatremia based on the EVEREST trial by constructing a cost-offset model to evaluate the impact of tolvaptan on hospital resource usage among HF patients.…”
Section: Introductionmentioning
confidence: 99%